NEW EARLY VARIETIES OF VEGETABLE PEA - A. G. Besedin; O. V. Putina (Овощи России)
The volume and structure of sown areas of vegetable pea varieties of different terms of ripening, selection of the Krymsk Experiment Plant Breeding Station, VIR in the southern region of Russia is shown. When creating new varieties, at present, priority is given to obtaining very early and early, in order to expand the conveyer of raw materials for processing. The merits of the breeding achievements created and included in the State Register are shown: a very early variety Prima (year of inclusion 2016) and an early Kudodesnik 2 (2018), which have already begun to be used in production. However, for processing enterprises in each group of ripening it is necessary to have 2-3 varieties. Therefore, we have set a goal - to create new varieties of vegetable peas of very early and early ripening periods, adaptive to the climatic conditions of the North Caucasus region. The studies were carried out from 2016 to 2018 in breeding fields (Krymsk Experiment Plant Breeding Station, VIR, Krasnodar region). Studied 10 varieties and lines. According to the results of evaluation in competitive variety testing (in 2016-2017), a very early grade of vegetable peas Izyuminka was transferred to the state test. The variety ripens 9 days earlier than the Alpha standard and surpasses it in yield (by 2.2 t / ha.). According to the competitive test held in 2017-2018, in 2019, the early variety Mayak was transferred to the state variety testing, which ripens 4 days earlier than the standard and is almost twice as high in yield. The use of these varieties in the processing industry will significantly increase the period of receipt of grain for processing.